Public Health's Response to HIV/AIDS in Ontario: A Critical Ethnography of Case Management Nursing - Juergensen, Linda (Université d'Ottawa / University of Ottawa, 2020)
HIV/AIDS is now widely recognized as a medically manageable condition. However, more than 2,000 new HIV infections are reported across Canada each year. A pressing issue in the public health response to HIV is how to better engage people at risk and living with the virus in testing, treatment, and support services. For this study, a critical ethnography was undertaken with 22 public health nurses involved in HIV case management in 14 public health units across Ontario. The objectives were to describe the experiences of case management nurses involved in the follow-up of people who test positive for HIV in public health units across Ontario and identify how public health policies shape the boundaries of nursing care and client outcomes in the response to HIV. A poststructuralist, feminist and critical geographical lens was employed to understand how different discourses determine the social and spatial organization of case management and structure the possibilities in nurses’ follow-up at the point-of-care. The main finding is evidence of two different sets of goals and measures in the public health response to HIV in Ontario: (1) a medical-epidemiological discourse tied to a biosecurity approach and goal of disease containment; and (2) a nursing discourse linked to a relational approach aimed at promoting meaningful engagement and ensuring people with HIV “feel supported.” The thesis of this study is that the hegemony of a biosecurity approach and singular biomedical indicator of success (an undetectable viral load) are contributing to the relegation of relational work and nurses’ efforts to support people who are unable or unwilling to engage in risk reduction measures to the margins of care. Strengthening the capacity of case management nurses to develop a relational approach and account for the diversity of emotional and social issues impacting the ability of people to live with HIV may be an important starting point for improving the outcomes of the public health response. The findings have implications for future research, policy, and practice in the areas of governmentality, public health nursing and efforts to end the “War on HIV.”
Keywords: Public health nursing; HIV/AIDS; Case management; Critical ethnography; Governmentality; Feminism; Critical Geography